An evaluation of the referral process in the emergency department. Issue 10 (19th July 2013) - Croft, Susan J; Barnes, Jane; Ginnis, Clare; Chatters, Robin; Mason, Suzanne
Abstract : Introduction: Making an effective telephone referral is an important skill for an emergency department (ED) clinician. It is essential for patient safety that the information is conveyed in a succinct manner to the correct inpatient specialty. The aim of this study was to assess: the impact of grade of staff making the referral; specialty referred to; and condition or patient problem. It also aimed to identify current problems or barriers in the referral process. Methods: This prospective study took place in one large teaching hospital in the UK. There were two parts: data collection to obtain information on each referral made by ED staff; and questionnaires administered to obtain opinions on the current referral process from both staff making and receiving the referrals. Results: Data were collected over 6 days and included 362 referrals. The mean evaluation of the referral process (scored 0–4) for all referrals was 3.34 (SD 0.95). 22 ED staff responding (64.7%) felt that some specialties were more difficult to refer to than others. 60.6% of non-ED staff accepting referrals felt they would like some form of senior ED screening process prior to referral compared with 20.6% of ED staff. The most common topics commented on were communication, education and process. Discussion: There are differences in understanding and opinion between ED and non-ED staff about the referral process. There are also factors which influence ease of referral: specialty referring to and patient problem. More intervention studies are required to identify solutions that can be implemented and sustained in routine practice.